Cross-listing and price efficiency: An institutional explanation - Diniz-Maganini, Natalia; Rasheed, Abdul A.; Yaşar, Mahmut; Hua Sheng, Hsia (Journal of International Business Studies, 2023)
Although many of the benefits of cross-listing have been examined in prior research, potential improvements in price efficiency have received less attention. We examine the differences in price efficiencies between American depositary receipts (ADRs) of foreign firms and the shares listed in their home markets. Based on multifractal detrended fluctuation analysis (MF-DFA) of the daily price of 200 ADRs and their domestically listed shares for the period from January 2010 to June 2019, we find that ADRs, in general, show greater price efficiency than their corresponding home market shares. Furthermore, our analysis shows that firms from civil law countries, firms from countries that have low levels of minority investor protection, and firms from emerging economies experience the greatest gains in price efficiency when they list their ADRs in the US compared to firms from common law countries, firms from countries with high levels of investor protection, and firms from developed countries. Furthermore, we also find that these efficiency improvements cannot be attributed to increases in liquidity. Instead, they can be mostly explained by institutional differences. Our results suggest that firms engage in institutional borrowing when their home-country markets are institutionally deficient.